The Kingfisher Children's Encyclopedia - John Paton 1914-; Jennifer Justice (UK Kingfisher Books, 1991)
Presents facts on more than 1300 subjects from Aardvark to Zoo. . General editor: John Paton . $29.95
"Revised one-volume edition first published in the United States in 1992. Originally published in multiple volumes in 1989"--T.p. verso.
Rev. ed. of: The Doubleday children's encyclopedia. 1st ed. in the U.S. 1990.
Includes indexes.
Keywords: Encyclopedias (3GdehShYGJs; Children's encyclopedias and dictionaries; General; Encyclopedias and dictionaries